1992
DOI: 10.1111/j.1467-9914.1992.tb00061.x
|View full text |Cite
|
Sign up to set email alerts
|

Wage Structure, Incomes Policy and Decentralised Bargaining: the Case of Greece

Abstract: Developments in Greek industrial relations suggest that decentralised bargaining is not a panacea. The manufacturing wage structure in Greece has an excep tional course associated with the rise of informal decentralised bargaining. Interindustry wage differentials increased in a period of incomes policies aiming to narrow the wage structure. The influence exerted by inflation and unemployment is, compared to past evidence from the US. and the U.K., quite unconventional. Under informal bargaining, high-wage pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…Moreover, Petrakis and Vlassis (1996) and Vlassis (1999) have shown that centralized bargaining can lead to wages above the market-clearing level, especially if coverage extension rules can be used to raise rivals' costs (Haucap et al, 2001;Roberts et al, 2000). 2 As far as employment and wage dynamics in Greek manufacturing are concerned, see Ioannou (1992Ioannou ( , 1995, Miaouli (1992Miaouli ( , 1993Miaouli ( , 1998, Kaskarelis (1993), Moschonas and Droucopoulos (1993), Jecchinis (1994), Demopoulos et al (1997) and Kouretas and Zarangas (2000). For an analysis of employment and minimum wage dynamics in Greece, see Kapopoulos et al (2000Kapopoulos et al ( , 2003.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Petrakis and Vlassis (1996) and Vlassis (1999) have shown that centralized bargaining can lead to wages above the market-clearing level, especially if coverage extension rules can be used to raise rivals' costs (Haucap et al, 2001;Roberts et al, 2000). 2 As far as employment and wage dynamics in Greek manufacturing are concerned, see Ioannou (1992Ioannou ( , 1995, Miaouli (1992Miaouli ( , 1993Miaouli ( , 1998, Kaskarelis (1993), Moschonas and Droucopoulos (1993), Jecchinis (1994), Demopoulos et al (1997) and Kouretas and Zarangas (2000). For an analysis of employment and minimum wage dynamics in Greece, see Kapopoulos et al (2000Kapopoulos et al ( , 2003.…”
Section: Discussionmentioning
confidence: 99%
“…12 In the case of competitive labour markets, and assuming that labour supply is inelastic in the short run, relative wages are used to attract workers in expanding sectors. However, in the period 1966-88 the Greek manufacturing labour market was operating far from the competitive model (Ioannou, 1995), and the manufacturing wage structure in Greece is classified in the same category as countries with considerable dispersion of inter-industry wages (Ioannou, 1992). 13 The effective labour force is proxied by a linear trend.…”
Section: Discussionmentioning
confidence: 99%
“…Greek unions are openly politicized (with, often, direct links between their leadership and the parties in government), while the institutional architecture of the labour market affords much monopoly power to public sector unions (centralized representation by a top‐level confederation that excludes private sector unions; union coverage effectively at 100 per cent; union density over three times higher than in the private sector — Matsaganis ). Thus, while formally public sector wages are set unilaterally by the government (Ioannou ), in practice unions exert a strong influence on public sector pay.…”
Section: Wage Setting and The Recent Pay Cuts In The Greek Public Sectormentioning
confidence: 99%
“…Besides these issues, this evidence is now quite dated, coming from a period with markedly different employment relations and before Greece's accession to European Economic and Monetary Union (EMU) in 2001. Since the late 1990s, Greece has followed an extensive privatization programme and has taken continuous steps towards labour market deregulation (Ioannou ; Monastiriotis and Pissarides ). Coupled with pressures applied to its labour market from membership in the Eurozone (Featherstone ), these developments ought to have altered significantly the valuation of skills and the appropriation of rents in the private and public sectors.…”
Section: Introductionmentioning
confidence: 99%